Localization of impacted permanent maxillary canine using single panoramic radiograph - Sudhakar S; Patil Karthikeya; Mahima V (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives : The objective in localization is selection of a suitable technique which has minimal radiation dose, cost and maximum details. Panoramic radiograph, being a screening radiograph, can satisfy the above needs. Taking this into consideration, the present study was done to evaluate the reliability of panoramic radiograph in localization of impacted permanent maxillary canines by applying the criteria suggested by Chaushu et al. and by comparing it with Clark′s rule. Materials and Methods : The study comprised of 114 subjects in the age group of 13-30 years of both the genders with 150 impacted canines visiting Department of Oral Medicine and Radiology during the study period. The study subjects were examined for clinically missing canine, and then confirmed with intra-oral peri-apical radiograph (IOPAR). Panoramic radiographs (for application of Chaushu et al. criteria) and IOPAR′s (for application of Clark′s rule) of the subjects were made and interpreted for parameters pertaining to the impacted canines. The data obtained was tabulated and subjected to statistical analysis using the statistical package for social sciences (SPSS) software. Results : Determination of the bucco-palatal position from panoramic radiographs, by applying Chaushu, et al. criteria, showed that localization in bucco-palatal position was possible for 96 of the 102 impacted canines placed in the middle and coronal zones. The remaining six impacted canines, three each in the middle and coronal zones, could not be localized as they showed overlapping in their range. By excluding them, the overall agreement worked out to be 94.11%. Localization was not possible for 48 impacted canines that lied in the apical zone. Conclusion : A single panoramic radiograph can serve as a reliable indicator for determining the bucco-palatal position of the impacted canines when they lie in the middle and coronal zones. When they lie in the apical zone it is recommended to explore their presence with other conventional or advanced imaging modalities.